Ferruginous bodies exert a strong proinflammatory effect. Issue 8 (18th April 2023) - Borelli, Violetta; Zangari, Martina; Bernareggi, Annalisa; Bardelli, Fabrizio; Vita, Francesca; Zabucchi, Giuliano
ABSTRACT: One of the main problems related to ferruginous-asbestos bodies (ABs) exposure is their potential pathogenetic role in asbestos-related diseases. The aim of this study was to examine whether purified ABs, might stimulate inflammatory cells. ABs were isolated by exploiting their magnetic properties, therefore avoiding the strong chemical treatment usually employed for this purpose. This latter treatment, which is based upon the digestion of organic matter with concentrated hypochlorite, may markedly modify the AB structure and consequently also their "in vivo" manifestations. ABs were found to induce secretion of human neutrophil granular component myeloperoxidase, as well as stimulate rat mast cell degranulation. Data demonstrated that by triggering secretory processes in inflammatory cells, purified ABs may play a role in the pathogenesis of asbestos-related diseases by continuing and enhancing the pro-inflammatory activity of the asbestos fibers.